If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 4 + 4x + 10(x + -1) = 0 Reorder the terms: x + 4 + 4x + 10(-1 + x) = 0 x + 4 + 4x + (-1 * 10 + x * 10) = 0 x + 4 + 4x + (-10 + 10x) = 0 Reorder the terms: 4 + -10 + x + 4x + 10x = 0 Combine like terms: 4 + -10 = -6 -6 + x + 4x + 10x = 0 Combine like terms: x + 4x = 5x -6 + 5x + 10x = 0 Combine like terms: 5x + 10x = 15x -6 + 15x = 0 Solving -6 + 15x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 15x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 15x = 0 + 6 15x = 0 + 6 Combine like terms: 0 + 6 = 6 15x = 6 Divide each side by '15'. x = 0.4 Simplifying x = 0.4
| (Y+3)(y-12)= | | x(x+4)=x^2+4 | | 24=g/2-14 | | 5k=0.35 | | y=6x^2+5x+7 | | 3(x-3)+3(x-3)+(x+3)+(x+3)=84 | | 2g=0.6 | | 4x+6x-8=1+7x | | 14f-66=5f+87 | | 2g+97=5g-98 | | 4x(2)=28 | | 8f+50=57f-97 | | 13z+13=23z-67 | | -(5/2)x+(7/3)=-(3/4)x-4 | | 40q+99=72q-93 | | 4b+41=7b-1 | | y=6x^2+7x+10 | | 4y+29=6y-71 | | 14j+68=56j-100 | | (6x^2+15x+4)/(x+2) | | 26x+16=51x-34 | | 8b+49=13b-91 | | 4y+3/5=3/4 | | 189/4 | | Y=8X^2-X-6 | | fx(6)=4x-2 | | 8a-24z= | | -1/4=189.5 | | 7x^2+5x-h=0 | | 4y=6/9 | | -2-2=-6+x | | 18x+6-21-2x= |